Epiretinal Membrane Management for Young Adult Patient: A Case Report - Zamzam, Avizena Muhammad; Ramzi Amin; A.K Ansyori (Sriwijaya Journal of Ophthalmology, 2024)
Introduction: Epiretinal membrane (ERM) is a condition where a thin fibrotic tissue layer appears on the surface of the macula, which causes a decrease in visual acuity. There are still limited data about the management of ERM due to its low incidence. We reported a case of epiretinal membranes in young adult patients. Case presentation: A 40-year-old male complained of blurry vision on the left eye since 6 months ago. His visual acuity was reduced, and a fundus photograph and macula OCT examination were performed. He was diagnosed with left eye epiretinal membrane and planned for left eye membrane peeling. The retinal break was found intraoperatively as a suspected predisposing factor. Conclusion: Management of severe ERM focuses on reducing metamorphopsia, improving visual acuity, and improving binocularity with pars plana vitrectomy combined with membrane peeling. At a young age, the predisposing factors for secondary development must be further identified.